Structural and ultrastructural morphological evaluation of giant anteater (Myrmecophaga tridactyla) prostate gland - Moura, Fernanda [UNESP]; Sampaio, Letícia [UNESP]; Kobayashi, Priscila [UNESP]; Laufer-Amorim, Renee [UNESP]; Ferreira, João Carlos [UNESP]; Watanabe, Tatiane Terumi Negrão; Fonseca-Alves, Carlos E. [UNESP] (MDPI, 2021)
The giant anteater (Myrmecophaga tridactyla) is a vulnerable species from Central and South America, and is considered possibly extinct in Belize, Guatemala, El Salvador, and Uruguay. Due to the species’ conservation and reproductive importance, this research aimed to characterize the morphology, histochemical, immunohistochemical, and ultrastructural feature of the giant anteater prostate gland. For this, we collected 11 giant anteater prostate glands and performed macroscopic, morphological, histochemical, immunohistochemical, and ultrastructural analysis. Nine prostate glands from an adult subject and two from young subjects were studied. Grossly, the adult giant anteater prostate gland is divided in two distinct zones; the central zones (composed mainly of ducts) and the peripheral zones (of acini formed by secretory cells). The secretory cells showed positive periodic acid–Schiff staining. Furthermore, the immunohistochemical characterization revealed a similar human prostate pattern, with p63 staining basal cells, uroplakin III (UPIII) superficial cells of prostatic urethra, androgen receptor (AR) expressing nucleus of secretory and stromal cells, and prostatic specific antigen (PSA) staining prostatic epithelial cells. Overall, our research provided an in-depth morphological description of the giant anteater’s prostate gland, providing valuable information for futures studies focused on giant anteater conservation.
Keywords: Conservation; Immunohistochemistry; Morphology; Reproduction; Xenarthra